Financial reporting frequency and its impact on the stock market: The case of Switzerland - Marisa Wilde (Universität Zürich, Institut für schweizerisches Bankwesen, 2005)
This paper examines the characteristics of firms that voluntarily provide interim financial reports. Based on a sample of Swiss companies, where semi-annual reports became mandatory in 1997, I document that before interim reports became mandatory, analyst coverage, i.e. analysts' demand for disclosure, affected the management decision on the regularity of interim reporting significantly. Higher information asymmetry, measured by the percentage of intangibles in the firm, increases the supply of interim reports. However, companies that provide more regular interim reports do not face less uncertainty among analysts, i.e. the standard deviation among analyst forecasts is not decreasing with reporting frequency. Further analyses reveal that analyst forecasts become significantly more accurate for firms with more regular interim reports. Finally, the results indicate that, voluntary interim reporters face significant negative abnormal returns around earnings announcement, when they report a profit, which fails to meet expectations. This underlines the importance of careful communication and earnings expectations guidance.
Keywords: 330; Voluntary Disclosure; Interim Reporting Frequency; Forecast Accuracy; Financial Reporting; Earnings Response Coefficient; Regulation; Aktienmarkt; Jahresabschluss; Schätzung; Schweiz